Handling Total Release Foggers - Frederick M. Fishel (EDIS)
PI-173, a 4-page illustrated fact sheet by Frederick M. Fishel, cautions about the risks of total release foggers (TRFs), also called "bug bombs," and common-sense precautions people can take to reduce risks before using one in any building. Includes additional sources of information. Published by the UF Department of Agronomy, March 2009.